Determinação dos compostos bioativos de ingá (Inga marginata Willd), por diferentes métodos de extração, caracterização química e citotoxicidade - Flores, Déborah Cristina Barcelos (2020)
The association between fruit ingestion and a healthy lifestyle reduces many types of diseases including degenerative ones, due to the bioactive compounds present. Ingá is considered an abundant fruit in several environments and it is known to have bioactive compounds such as as phenolic compounds (flavonoids such as anthocyanins, flavonols and their derivatives), phenolic acids (benzoic, cinnamic acids and their derivatives) and coumarins. Among phenolics, flavonoids, phenolic acids, tannins and tocopherols stand out as the most common antioxidants. Thus, this work aimed to determine the bioactive compounds obtained by different extraction methods, in addition to the characterization the chemical profile and the cytotoxicity of the shell and pulp fraction, and the Ingá seed. The toxicity of the extracts in the 3T3 cell line was analyzed by cell viability through MTT and NRU tests. The hydroethanolic extracts were prepared at 70% (v/v) for the extraction of bioactive compounds by conventional extraction, ultrasound and focused microwave. Analysis of total phenolic compounds, flavonoids, DPPH (IC50) and ORAC were performed, evaluating the time and temperature, and the identification of the chemical profile by ESI-TOF-MS mass spectrometry. The extract of the peel and pulp fraction of Ingá in all concentrations was not cytotoxic, since the seed extract showed toxicity for both tests, therefore, the research was carried out only with the extracts of the peel and pulp. The extract obtained through conventional extraction had a higher content of total phenolics, flavonoids and greater antioxidant capacity at 60 ºC for 5 minutes. The temperature had a significant effect for all determinations, while time had a significant effect only for the determination flavonoids, with an interaction between time and temperature. For ultrasound extraction, the best condition was at a temperature of 60 ºC for 5 minutes, in which higher levels of bioactive compounds were obtained. Only temperature had a significant effect, time only had an effect and interaction with temperature in determining flavonoids. The extract obtained by the focused microwave extraction showed a higher content of total phenolics, flavonoids and antioxidant capacity at 60 ºC for 25 minutes. In this extraction method, as the time and temperature increased, the content of the extracted compounds increased, presenting a significant effect and interaction between the variables for the total phenolics. In addition to the determination of the bioactive compounds, the extracts obtained by different extraction methods were also characterized, and in the conventional extraction 7 compounds were identified, in the extraction by ultrasound and focused microwave extraction 11 equal compounds were found, regardless of the method. In this sense, it can be inferred that the Ingá peel and pulp fraction is a good source of bioactive compounds with antioxidant action, being of great interest in the extraction of these compounds for application in food products, in addition to contributing to the reduction of waste.